Application of Ultrasonic Tomography to Display Tomogram of Liquid/Solid Flow Regime by Using Linear Back Projection - Rubiah, Ahmad; Yasmin, Abdul Wahab (2013)

(untitled)
This paper present on software implementation to display tomogram of solid/liquid flow regime by using ultrasonic tomography (UT).